Hospitality Students' Perceptions Towards the Application of Communicative Language Teaching (CLT) (A Case Study at SMKN 5 Barru) - Rafidah Binti Rostan (Journal on Education, 2023)
This research aims to find out the students' perceptions about the implementation of communicative language teaching (CLT) to develop their speaking skills. The participants in this study involved twelfth-grade (XII) students from hospitality program at SMK N 5 Barru. This research conducted a descriptive qualitative approach and the data was gathered by observation using field notes and interviews. Data reduction, data display, and conclusion drawing were used in analyzing the data. The findings indicated that most of the hospitality students agreed the application of CLT in classroom activities could help them in developing their language skills and self-confidence even though they found it quite challenging to implement in their learning process and thus, still required their teacher to use code-switching during classroom activities. Moreover, the students mostly favored active discussion activities and worked in pairs or groups that focused on their fields of study with the integration of additional tools, such as online platforms and applications to make their learning process more exciting. The results of this study showed that the hospitality students had positive perceptions toward the use of CLT that applied by the English teacher, as these enhanced their language learning experience and progressively improved the hospitality students speaking abilities in practicing the target language.